If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 = 41 Reorder the terms: 1 + 3x = 41 Solving 1 + 3x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 41 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 41 + -1 3x = 41 + -1 Combine like terms: 41 + -1 = 40 3x = 40 Divide each side by '3'. x = 13.33333333 Simplifying x = 13.33333333
| 31=4t+3 | | x-x^2-x^3=0 | | -x^2=-3x+5 | | 750-50*24= | | -11/t=8/48 | | -3p+8=6-(8p+5) | | 16(2x-4)=4(8x+9) | | 6x+3+x=2+5x+5 | | 0.20t^2-45.0t+1000=0 | | 0.20t^2-45.0t=1000 | | 9+10s-4=9s+47-6s | | -16t^2+3t+1.3=0 | | -7(x+1)-13=26+3 | | -32+28=4 | | y/15+6=y/6+12 | | -9=-6+3x | | 16x^4=y^2 | | 0=2(3x-5)+8(4x+7) | | -16t^2+3t+1.3=h(t) | | 12+m/4=3d-1/2 | | (2x-3)(x+3)=3 | | 4(a+3)=6(a-(5-a)) | | 6(3+v)+36v=13v | | 7r-8r=6 | | 5xy-3y-4=0 | | X-3/5+3/5=-x/2 | | -5t-26=18t | | -(100/-4) | | 3x+9=15forx | | 0=16t^2+44t-24 | | -3/4+7/3 | | 4=2a+37 |